Successful treatment of recurrent renal stones with Cinacalcet in a patient with primary hyperparathyroidism. (12th August 2016) - Chauhan, Priyesh; Gittoes, Neil J; Geberhiwot, Tarekegn
Abstract : A man aged 72 years with long-standing primary hyperparathyroidism (HPT), a background of recurrent bilateral renal stones and failed parathyroid surgery is described. During the 27 months preceding treatment, episodes of renal colic became increasingly frequent and he required multiple surgical interventions. Given the lack of medical therapies to definitively treat his symptoms, he was started on a trial of the calcimimetic, Cinacalcet. Cinacalcet has previously been shown to reduce hypercalcaemia in patients with primary HPT. Despite this, there is a paucity of evidence to suggest that its use is associated with a long-term reduction in urinary calcium excretion and renal stone recurrence. In our case, within 4 months of starting treatment, serum and urinary calcium had normalised and parathyroid hormone concentrations were within reference ranges. To date, over a 50-month treatment period, there has been a complete cessation in stone formation, and no further urological intervention has been required.